Association of Exome Sequences With Cardiovascular Traits Among Blacks in the Jackson Heart Study. (August 2016) - Peloso, Gina M.; Lange, Leslie A.; Varga, Tibor V.; Nickerson, Deborah A.; Smith, Joshua D.; Griswold, Michael E.; Musani, Solomon; Polfus, Linda M.; Mei, Hao; Gabriel, Stacey; Quarells, Rakale Collins; Altshuler, David; et al.
Abstract : Background—: The correlation of null alleles with human phenotypes can provide insight into gene function in humans. In individuals of African ancestry, we set out to identify null and damaging missense variants, and test these variants for association with a range of cardiovascular phenotypes. Methods and Results—: We performed whole-exome sequencing in 3223 black individuals from the Jackson Heart Study and found a total of 729 666 variant sites with minor allele frequency <5%, including 17 263 null variants and 49 929 missense variants predicted to be damaging by in silico algorithms. We tested null and damaging missense variants within each gene for association with 36 cardiovascular traits. We found 3 associations that met our prespecified level of significance (α=1.1×10 −7 ). Null and damaging missense variants in PCSK9 were associated with 36 mg/dL lower low-density lipoprotein cholesterol ( P =3×10 −21 ). Three individuals in their 50s with complete PCSK9 deficiency (each compound heterozygote for PCSK9 p.Y142X and p.C679X) were identified, with one having a coronary artery calcification score in the 83rd percentile despite a low-density lipoprotein cholesterol of 32 mg/dL. A damaging missense variant in HBQ1 (p.G52A) was associated with a 2 pg/cell lower mean corpuscular hemoglobin ( P =9×10 −13 ) and rare damaging missense variants in VPS13A with higher red blood cell distribution width ( P =9.9×10 –8 ). Conclusions—: A limited number of null/damaging alleles with a large effect on cardiovascular traits were detectable in ≈3000 black individuals. Abstract : Supplemental Digital Content is available in the text.